Impact of castor bean cake fertilizer as side-dressing on cauliflower yield and quality in organic farming systems - Candian, Joara Secchi; Nakada-Freitas, Pâmela Gomes [UNESP]; da Silva, Andre Luiz Biscaia Ribeiro; Cardoso, Antonio Ismael Inácio [UNESP] (Southern Cross Publishing, 2024)
The significance of organic production has grown significantly in the past decade. Therefore, research on organic fertilizer, mainly as side-dress, has gained more importance. Castor bean cake is a fertilizer rich in nitrogen and organic matter. This cake has been used as an organic fertilizer once it has higher mineralization rate compared to other sources such as as sugarcane bagasse and cattle manure. We studied rate and application time of castor bean cake on the production, physicochemical characteristics, macronutrient contents, and accumulation of cauliflower in an organic system. Ten treatments were studied, in a 3 x 3 + 1 factorial design, with three rates of castor bean cake (1290, 2580 and 3870 kg ha-1) combined with three application times as side-dress (single application at 30 or 45 days after transplanting (DAT) and split application at 30 and 45 DAT), as well as a control (without fertilizer). The experimental design was randomized blocks with four replications. This study measured cycle, leaf number, inflorescence diameter, height, fresh and dry biomass, vegetative part (stem and leaves) fresh and dry biomass, pH, titratable acidity (TA), ascorbic acid (AA), soluble solids (SS), maturation index/ratio, reducing sugar contents (RSC), protein, macronutrient content, and accumulation in inflorescence. The maximum inflorescence fresh biomass was highest at 3015 kg ha-1, while the maximum height and diameter were at 3785 and 3335 kg ha-1, respectively. The highest rates of castor bean cake increased TA, while it decreased RSC, AA, and inflorescence ratio. The decreasing order of accumulated nutrients on inflorescence was K>N>P≈Ca>Mg>S, with maximums of 1.48; 1.03; 0.15; 0.14; 0.08 and 0.06 g inflorescence-1, respectively. The rates of 3000 to 3800 kg ha-1 of castor bean cake increased production regardless time of application. Time factor had low influence on the physicochemical characteristics, macronutrient contents, and accumulations in inflorescence. Growers are recommended to apply 3 to 4 t ha-1 of castor bean cake.
Keywords: Brassica oleracea var. botrytis; nitrogen; nutrition; organic fertilizer; physical-chemistry analysis